Education on Making Bay Leaf Tea for Gout Therapy Arthritis in Cadres in Klapagading Kulon Village, Wangon District, Banyumas Regency - Adhelia Clarysha; Wasis Eko Kurniawan; Madyo Maryoto (Sean Institute, 2025)
The community service program, titled